Multiscore, a gene ranker powered by artificial intelligence and real-world clinical data, shows high sensitivity for the molecular diagnosis of Mendelian disorders in nearly 10,000 exomes and genomes - Vincent D. Ustach; Maria J. Guillen Sacoto; Stephen McGee; Vladimir G. Gainullin; Kevin Arvai; Amber Begtrup; Flavia M. Facio; Matthew Greenberg; Hákon Guðbjartsson; Kirsty McWalter; Francisca Millán; Kristin Monaghan; et al. (Human Genetics, 2026)

Distribution, abundance and ecological associations among two species of native mussels (Gonidea angulata and Margaritifera falcata) and one invasive clam species (Corbicula fluminea) in the Columbia River Basin, North America - Nathaniel G. Neal; Stephen M. Bollens; Alexa N. Maine; Timothy D. Counihan; Gretchen Rollwagen-Bollens (Aquatic Sciences, 2026)
Native freshwater mussels are declining globally, thus, determining factors associated with bivalve distribution and abundance is critical for native mussel conservation. In the Columbia River Basin, Gonidea angulata (western ridged mussel) is highly threatened, while Margaritifera falcata (western pearlshell) and the invasive clam Corbicula fluminea (Asian clam) are more common. We conducted 147 snorkel surveys, collected environmental data and performed statistical tests to quantify which variables were significantly associated with presence and abundance of these taxa. Variation in G. angulata presence and/or abundance were best explained by impervious surface proportion and annual air temperatures (mean and maximum). Margaritifera falcata presence and/or abundance were best explained by host fish presence, G. angulata presence, dissolved oxygen, and elevation. Corbicula fluminea presence and/or abundance were best explained by substrate size, impervious surface proportion, and annual air temperatures. Microhabitat and landscape variables explained some variation in bivalve presence and abundance, but the inclusion of watershed as a random effect increased the explanatory value. Consideration of species-specific habitat preferences and watershed-level variation could improve regional management in response to native mussel declines and invasive clam expansion.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Green fluorescent proteins show divergent patterns among species and strains of Porites from the Great Barrier Reef - Samantha Goyen; Erin E. Chille; Timothy G. Stephens; Shrinivas Nandi; Line K. Bay; Debashish Bhattacharya (Coral Reefs, 2026)
GFP-like and RFP-like proteins serve diverse functional roles in corals, including photoprotection, prey capture, and algal symbiont attraction. This study investigated the diversity of biofluorescence patterns in 27 coral colonies of Porites cf. lutea and Porites cf. lobata from the Great Barrier Reef, Australia. We used comparative methods to characterize the extant fluorescence patterns under blue and green light for excitation, their relationship to the Porites phylogeny built using host animal 18S-28S rDNA sequence data. We also studied the impact of thermal stress on green and red fluorescence in a single coral genotype to assess stability of the observed signal. Overall, we identified six broad fluorescence patterns: star, uniform, absent, tentacles, oral region, and tentacle tips. Population analyses demonstrate that a single lineage of Porites may express divergent and distinct GFP-like patterns that are shared by all polyps in a colony. This suggests that biofluorescent proteins may confer an array of adaptive functions that allow Porites species to thrive in different ecosystems under different stressors. The reorganization of both green and red fluorescence distributions to uniform patterning under thermal stress suggests these proteins may provide a biomarker of thermal stress. Thus, the potential for GFP/green fluorescence and RFP/red fluorescence screening as a non-invasive tool to assess reef health and adaptive responses warrants further investigation, particularly in the context of climate change-driven stress events.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

The composition of gases from a diffusion flame above longleaf pine needle fuel beds - David.R. Weise; Thomas H. Fletcher; Timothy J. Johnson; WeiMin Hao; Russell G. Tonkyn; Catherine A. Banach; Javier Palarea-Albaladejo; Mahsa Alizadeh; Stephen Baker (Fuel, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Genetic Transfer in Action: Uncovering DNA Flow in an Extremophilic Microbial Community - Julia Van Etten; Timothy G. Stephens; Debashish Bhattacharya (Environmental Microbiology, 2025)
Horizontal genetic transfer (HGT) is a significant driver of genomic novelty in all domains of life. HGT has been investigated in many studies however, the focus has been on conspicuous protein‐coding DNA transfers that often prove to be adaptive in recipient organisms and are therefore fixed longer‐term in lineages. These results comprise a subclass of HGTs and do not represent exhaustive (coding and non‐coding) DNA transfer and its impact on ecology. Uncovering exhaustive HGT can provide key insights into the connectivity of genomes in communities and how these transfers may occur. In this study, we use the term frequency‐inverse document frequency (TF‐IDF) technique, that has been used successfully to mine DNA transfers within real and simulated high‐quality prokaryote genomes, to search for exhaustive HGTs within an extremophilic microbial community. We establish a pipeline for validating transfers identified using this approach. We find that most DNA transfers are within‐domain and involve non‐coding DNA. A relatively high proportion of the predicted protein‐coding HGTs appear to encode transposase activity, restriction‐modification system components, and biofilm formation functions. Our study demonstrates the utility of the TF‐IDF approach for HGT detection and provides insights into the mechanisms of recent DNA transfer.

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Diverse fates of ancient horizontal gene transfers in extremophilic red algae - Julia Van Etten; Timothy G. Stephens; Erin Chille; Anna Lipzen; Daniel Peterson; Kerrie Barry; Igor V. Grigoriev; Debashish Bhattacharya (Environmental Microbiology, 2024)
Horizontal genetic transfer (HGT) is a common phenomenon in eukaryotic genomes. However, the mechanisms by which HGT‐derived genes persist and integrate into other pathways remain unclear. This topic is of significant interest because, over time, the stressors that initially favoured the fixation of HGT may diminish or disappear. Despite this, the foreign genes may continue to exist if they become part of a broader stress response or other pathways. The conventional model suggests that the acquisition of HGT equates to adaptation. However, this model may evolve into more complex interactions between gene products, a concept we refer to as the ‘Integrated HGT Model’ (IHM). To explore this concept further, we studied specialized HGT‐derived genes that encode heavy metal detoxification functions. The recruitment of these genes into other pathways could provide clear examples of IHM. In our study, we exposed two anciently diverged species of polyextremophilic red algae from the Galdieria genus to arsenic and mercury stress in laboratory cultures. We then analysed the transcriptome data using differential and coexpression analysis. Our findings revealed that mercury detoxification follows a ‘one gene‐one function’ model, resulting in an indivisible response. In contrast, the ars H gene in the arsenite response pathway demonstrated a complex pattern of duplication, divergence and potential neofunctionalization, consistent with the IHM. Our research sheds light on the fate and integration of ancient HGTs, providing a novel perspective on the ecology of extremophiles.

Facultative lifestyle drives diversity of coral algal symbionts - Debashish Bhattacharya; Timothy G. Stephens; Erin E. Chille; L. Felipe Benites; Cheong Xin Chan (Trends in Ecology & Evolution, 2024)

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

The spontaneous mouse mutant low set ears (Lse) is caused by tandem duplication of Fgf3 and Fgf4 - Alana Luzzio; Sarah Edie; Kristina Palmer; L. Brianna Caddle; Rachel Urban; Leslie O. Goodwin; Ian C. Welsh; Laura G. Reinholdt; David E. Bergstrom; Timothy C. Cox; Leah Rae Donahue; Stephen A. Murray (Mammalian Genome, 2023)

Contribution of soil bacteria to the atmosphere across biomes - Stephen D.J. Archer; Kevin C. Lee; Tancredi Caruso; Antonio Alcami; Jonathan G. Araya; S. Craig Cary; Don A. Cowan; Claudia Etchebehere; Batdelger Gantsetseg; Benito Gomez-Silva; Sean Hartery; Ian D. Hogg; et al. (Science of The Total Environment, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Projecting climate change impacts from physics to fisheries: A view from three California Current fisheries - James A. Smith; Mercedes Pozo Buil; Barbara Muhling; Desiree Tommasi; Stephanie Brodie; Timothy H. Frawley; Jerome Fiechter; Stefan Koenigstein; Amber Himes-Cornell; Michael A. Alexander; Steven J. Bograd; Nathalí Cordero Quirós; et al. (Progress in Oceanography, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Life on the edge: Hawaiian model for coral evolution - Debashish Bhattacharya; Timothy G. Stephens; Amanda I. Tinoco; Robert H. Richmond; Phillip A. Cleves (Limnology and Oceanography, 2022)
Degradation and loss of coral reefs due to climate change and other anthropogenic stressors has fueled genomics, proteomics, and genetics research to investigate coral stress response pathways and to identify resilient species, genotypes, and populations to restore these biodiverse ecosystems. Much of the research and conservation effort has understandably focused on the most taxonomically rich regions, such as the Great Barrier Reef in Australia and the Coral Triangle in the western Pacific. These ecosystems are analogous to tropical rainforests that also house enormous biodiversity and complex biotic interactions among different trophic levels. An alternative model ecosystem for studying coral reef biology is the relatively species poor but abundant coral reefs in the Hawaiian Archipelago that exist at the northern edge of the Indo‐Pacific coral distribution. The Hawaiian Islands are the world's most isolated archipelago, geographically isolated from other Pacific reef systems. This region houses about 80 species of scleractinian corals in three dominant genera ( Porites , Montipora , and Pocillopora ). Here we briefly review knowledge about the Hawaiian coral fauna with a focus on our model species, the rice coral Montipora capitata . We suggest that this simpler, relatively isolated reef system provides an ideal platform for advancing coral biology and conservation using multi‐omics and genetic tools.

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Changes to the structure and function of an albacore fishery reveal shifting social‐ecological realities for Pacific Northwest fishermen - Timothy H. Frawley; Barbara A. Muhling; Stephanie Brodie; Mary C. Fisher; Desiree Tommasi; Gwendal Le Fol; Elliott L. Hazen; Stephen S. Stohs; Elena M. Finkbeiner; Michael G. Jacox (Fish and Fisheries, 2021)
Marine fisheries around the globe are increasingly exposed to external drivers of social and ecological change. Though diversification and flexibility have historically helped marine resource users negotiate risk and adversity, much of modern fisheries management treats fishermen as specialists using specific gear types to target specific species. Here, we describe the evolution of harvest portfolios amongst Pacific Northwest fishermen over 35+ years with explicit attention to changes in the structure and function of the albacore ( Thunnus alalunga, Scombridae) troll and pole‐and‐line fishery. Our analysis indicates that recent social–ecological changes have had heterogenous impacts upon the livelihood strategies favoured by different segments of regional fishing fleets. As ecological change and regulatory reform have restricted access to a number of fisheries, many of the regional small ( 60 ft) targeting albacore are more specialized now than previously observed, even as participation in multiple fisheries has become increasingly common for this size class. In describing divergent trajectories associated with the albacore fishery, one of the US West Coast's last open‐access fisheries, we highlight the diverse strategies and mechanisms utilized to sustain fisheries livelihoods in the modern era while arguing that alternative approaches to management and licensing may be required to maintain the viability of small‐scale fishing operations worldwide moving forward.

Persistent COVID-19-associated neurocognitive symptoms in non-hospitalized patients - Joanna Hellmuth; T. Allen Barnett; Breton M. Asken; J. Daniel Kelly; Leonel Torres; Melanie L. Stephens; Bryan Greenhouse; Jeffrey N. Martin; Felicia C. Chow; Steven G. Deeks; Meredith Greene; Bruce L. Miller; et al. (Journal of NeuroVirology, 2021)
As cases of coronavirus disease 2019 (COVID-19) mount worldwide, attention is needed on potential long-term neurologic impacts for the majority of patients who experience mild to moderate illness managed as outpatients. To date, there has not been discussion of persistent neurocognitive deficits in patients with milder COVID-19. We present two cases of non-hospitalized patients recovering from COVID-19 with persistent neurocognitive symptoms. Commonly used cognitive screens were normal, while more detailed testing revealed working memory and executive functioning deficits. An observational cohort study of individuals recovering from COVID-19 (14 or more days following symptom onset) identified that among the first 100 individuals enrolled, 14 were non-hospitalized patients reporting persistent cognitive issues. These 14 participants had a median age of 39 years (interquartile range: 35–56), and cognitive symptoms were present for at least a median of 98 days (interquartile range: 71–120 following acute COVID-19 symptoms); no participants with follow-up evaluation reported symptom resolution. We discuss potential mechanisms to be explored in future studies, including direct viral effects, indirect consequences of immune activation, and immune dysregulation causing auto-antibody production.

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Biocultural diversity and food sovereignty: a case study of human-plant relations in northwestern Ethiopia - Morgan L. Ruelle; Karim-Aly Kassam; Stephen J. Morreale; Zemede Asfaw; Alison G. Power; Timothy J. Fahey (Food Security, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Effects of new-generation TMEM16A inhibitors on calcium-activated chloride currents in rabbit urethral interstitial cells of Cajal - Stephen Fedigan; Eamonn Bradley; Timothy Webb; Roddy J. Large; Mark A. Hollywood; Keith D. Thornbury; Noel G. McHale; Gerard P. Sergeant (Pflügers Archiv - European Journal of Physiology, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Carbon storage in tropical forests correlates with taxonomic diversity and functional dominance on a global scale - Kyle C. Cavanaugh; J. Stephen Gosnell; Samantha L. Davis; Jorge Ahumada; Patrick Boundja; David B. Clark; Badru Mugerwa; Patrick A. Jansen; Timothy G. O'Brien; Francesco Rovero; Douglas Sheil; Rodolfo Vasquez; et al. (Global Ecology and Biogeography, 2014)
Aim We examined (1) the relationships between aboveground tropical forest C storage, biodiversity and environmental drivers and (2) how these relationships inform theory concerning ecosystem function and biodiversity. Experiments have shown that there is a positive relationship between biodiversity and ecosystem functioning, but intense debate exists on the underlying mechanisms. While some argue that mechanisms such as niche complementarity increase ecosystem function, others argue that these relationships are a selection effect. Location Eleven tropical forests in the A mericas, A frica and A sia. Methods We analysed the correlates of biodiversity and carbon storage in tropical forests using data from 59 1‐ha tree plots from a standardized global tropical forest biodiversity‐monitoring network. We examined taxonomic and functional diversity, aboveground C storage and environmental variables in order to determine the relationships between biodiversity and carbon storage in natural (non‐plantation) tropical forests. Results We found that aboveground C storage in tropical forests increased with both taxonomic diversity and functional dominance, specifically the dominance of genera with large maximum diameters, after potential environmental drivers were accounted for (final model R 2 = 0.38, P Main conclusions Our results suggest that niche complementarity and the selection effect are not mutually exclusive: they both play a role in structuring tropical forests. While previous studies have documented relationships between diversity and C storage, these have largely been conducted on small scales in biomes that are relatively species poor compared with tropical forests (e.g. grasslands and temperate or boreal forests). Our results demonstrate that these positive biodiversity–ecosystem functioning relationships are also present in hyperdiverse systems on spatial scales relevant to conservation and management. This insight can be used to inform the conservation and management of tropical forests, which play a critical role in the global carbon cycle and are some of the biologically richest ecosystems on the planet.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Early life sun exposure, vitamin D-related gene variants, and risk of non-Hodgkin lymphoma - Jennifer L. Kelly; Matthew T. Drake; Zachary S. Fredericksen; Yan W. Asmann; Mark Liebow; Tait D. Shanafelt; Andrew L. Feldman; Stephen M. Ansell; William R. Macon; Megan M. Herr; Alice H. Wang; Grzegorz S. Nowakowski; et al. (Cancer Causes & Control, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Pre-clinical Implants of the Levitronix PediVAS® Pediatric Ventricular Assist Device: Strategy for Regulatory Approval - Timothy M. Maul; Ergin Kocyildirim; John D. Marks; Shawn G. Bengston; Salim E. Olia; Patrick M. Callahan; Marina V. Kameneva; Stephen Franklin; Harvey S. Borovetz; Kurt A. Dasse; Peter D. Wearden (Cardiovascular Engineering and Technology, 2011)

Chaperonins from an Antarctic archaeon are predominantly monomeric: crystal structure of an open state monomer - Oliver Pilak; Stephen J. Harrop; Khawar S. Siddiqui; Kevin Chong; Davide De Francisci; Dominic Burg; Timothy J. Williams; Ricardo Cavicchioli; Paul M. G. Curmi (Environmental Microbiology, 2011)
Summary Archaea are abundant in permanently cold environments. The Antarctic methanogen, Methanococcoides burtonii , has proven an excellent model for studying molecular mechanisms of cold adaptation. Methanococcoides burtonii contains three group II chaperonins that diverged prior to its closest orthologues from mesophilic Methanosarcina spp. The relative abundance of the three chaperonins shows little dependence on organism growth temperature, except at the highest temperatures, where the most thermally stable chaperonin increases in abundance. In vitro and in vivo , the M. burtonii chaperonins are predominantly monomeric, with only 23–33% oligomeric, thereby differing from other archaea where an oligomeric ring form is dominant. The crystal structure of an N‐terminally truncated chaperonin reveals a monomeric protein with a fully open nucleotide binding site. When compared with closed state group II chaperonin structures, a large‐scale ∼30° rotation between the equatorial and intermediate domains is observed resulting in an open nucleotide binding site. This is analogous to the transition observed between open and closed states of group I chaperonins but contrasts with recent archaeal group II chaperonin open state ring structures. The predominance of monomeric form and the ability to adopt a fully open nucleotide site appear to be unique features of the M. burtonii group II chaperonins.

The RNA polymerase subunits E/F from the Antarctic archaeon Methanococcoides burtonii bind to specific species of mRNA - Davide De Francisci; Stefano Campanaro; Geoff Kornfeld; Khawar S. Siddiqui; Timothy J. Williams; Haluk Ertan; Laura Treu; Oliver Pilak; Federico M. Lauro; Stephen J. Harrop; Paul M. G. Curmi; Ricardo Cavicchioli (Environmental Microbiology, 2011)
Summary RNA polymerase in Archaea is composed of 11 or 12 subunits – 9 or 10 that form the core, and a heterodimer formed from subunits E and F that associates with the core and can interact with general transcription factors and facilitate transcription. While the ability of the heterodimer to bind RNA has been demonstrated, it has not been determined whether it can recognize specific RNA targets. In this study we used a recombinant archaeal Mb RpoE/F to capture cellular mRNA in vitro and a microarray to determine which transcripts it specifically binds. Only transcripts for 117 genes (4% of the total) representing 48 regions of the genome were bound by Mb RpoE/F. The transcripts represented important genes in a number of functional classes: methanogenesis, cofactor biosynthesis, nucleotide metabolism, transcription, translation, import/export. The arrangement and characteristics (e.g. codon and amino acid usage) of genes relative to the putative origin of replication indicate that Mb RpoE/F preferentially binds to mRNA of genes whose expression may be important for cellular fitness. We also compared the biophysical properties of RpoE/F from M. burtonii and Methanocaldococcus jannaschii , demonstrating a 50°C difference in their apparent melting temperatures. By using Mb RpoE/F to capture and characterize cellular RNA we have identified a previously unknown functional property of the Mb RpoE/F heterodimer.

Hybridization and polyploidy as drivers of continuing evolution and speciation in Sorbus - ASHLEY ROBERTSON; TIMOTHY C. G. RICH; ALEXANDRA M. ALLEN; LIBBY HOUSTON; CAT ROBERTS; JON R. BRIDLE; STEPHEN A. HARRIS; SIMON J. HISCOCK (Molecular Ecology, 2010)

Adaptive differences in gene expression in European flounder ( Platichthys flesus ) - PETER F. LARSEN; EINAR E. NIELSEN; TIMOTHY D. WILLIAMS; JAKOB HEMMER‐HANSEN; JAMES K. CHIPMAN; MOGENS KRUHØFFER; PETER GRØNKJÆR; STEPHEN G. GEORGE; LARS DYRSKJØT; VOLKER LOESCHCKE (Molecular Ecology, 2007)
Population structure was previously believed to be very limited or absent in classical marine fishes, but recently, evidence of weakly differentiated local populations has been accumulating using noncoding microsatellite markers. However, the evolutionary significance of such minute genetic differences remains unknown. Therefore, in order to elucidate the relationship between genetic markers and adaptive divergence among populations of marine fishes, we combined cDNA microarray and microsatellite analysis in European flounders ( Platichthys flesus ). We demonstrate that despite extremely low levels of neutral genetic divergence, a high number of genes were significantly differentially expressed between North Sea and Baltic Sea flounders maintained in a long‐term reciprocal transplantation experiment mimicking natural salinities. Several of the differentially regulated genes could be directly linked to fitness traits. These findings demonstrate that flounders, despite little neutral genetic divergence between populations, are differently adapted to local environmental conditions and imply that adaptation in gene expression could be common in other marine organisms with similar low levels of population subdivision.

Estimating the Efficiency of Fish Cross-Species cDNA Microarray Hybridization - Raphael Cohen; Vered Chalifa-Caspi; Timothy D. Williams; Meirav Auslander; Stephen G. George; James K. Chipman; Moshe Tom (Marine Biotechnology, 2007)